CRM Practices in the Asia Pacific Industry - A Conceptual Study - Agnes, R. Ruma (Indian Journal of Marketing, 2010)
Customer Relationship Management (CRM) is not new to the world of business. It is a managerial philosophy that enables a firm to become thoroughly familiar with its customers. This concept is currently gaining widespread popularity in many industries. Firms that embrace CRM strive to provide consistent and personal customer service over time and across multiple touch points. Insurance Industry is one such Industry which involves many touch points, such as agents, call centers, representatives etc. Here, it is very essential to efficiently manage good relationship with the customers to ensure profitability and growth of the Insurance companies. Asia Pacific Region, which includes the Indian, Chinese, Malaysian, Australian markets and few others is growing rapidly. One of the reasons for this is the pace of general economic development, which far exceeds the growth rates customary in Western Europe or North America. This paper briefly discusses the concepts of CRM and its importance to the organization. Also, a general outline of the Insurance industry in the Asia-Pacific region is exposed in this article. Further to this, the challenges and issues faced in implementation of CRM structure in an organization are also dealt in this paper with suitable examples from the industry.